Childhood Invasive Bacterial Disease in Kathmandu, Nepal (2005–2013). Issue 3 (March 2022) - Carter, Michael J.; Gurung, Meeru; Pokhrel, Bhishma; Bijukchhe, Sanjeev Man; Karmacharya, Sudhir; Khadka, Bijay; Maharjan, Anju; Bhattarai, Suraj; Shrestha, Swosti; Khadka, Bibek; Khulal, Animesh; Gurung, Sunaina; et al.
Abstract : Background: Invasive bacterial disease (IBD; including pneumonia, meningitis, sepsis) is a major cause of morbidity and mortality in children in low-income countries. Methods: We analyzed data from a surveillance study of suspected community-acquired IBD in children <15 years of age in Kathmandu, Nepal, from 2005 to 2013 before introduction of pneumococcal conjugate vaccines (PCV). We detailed the serotype-specific distribution of invasive pneumococcal disease (IPD) and incorporated antigen and PCR testing of cerebrospinal fluid (CSF) from children with meningitis. Results: Enhanced surveillance of IBD was undertaken during 2005–2006 and 2010–2013. During enhanced surveillance, a total of 7956 children were recruited of whom 7754 had blood or CSF culture results available for analysis, and 342 (4%) had a pathogen isolated. From 2007 to 2009, all 376 positive culture results were available, with 259 pathogens isolated (and 117 contaminants). Salmonella enterica serovar Typhi was the most prevalent pathogen isolated (167 cases, 28% of pathogens), followed by Streptococcus pneumoniae (98 cases, 16% pathogens). Approximately, 73% and 78% of pneumococcal serotypes were contained in 10-valent and 13-valent PCV, respectively. Most cases of invasive pneumococcal disease (IPD) were among children ≥5 years of age from 2008 onward. Antigen and PCR testing of CSF for pneumococci, Haemophilus influenzae type b and meningococci increased the number of these pathogens identified from 33 (culture) to 68 (culture/antigen/PCR testing). Conclusions: S. enterica serovar Typhi and S. pneumoniae accounted for 44% of pathogens isolated. Most pneumococcal isolates were of serotypes contained in PCVs. Antigen and PCR testing of CSF improves sensitivity for IBD pathogens.